Croatian rotatory oblique three-dimensional osteotomy (CROTO) – a modified Wilson’s osteotomy for adult hallux valgus intended to prevent dorsal displacement of the distal fragment and to reduce shortening of the first metatarsal bone - Robert Kolundžić; Mladen Mađarević; Vladimir Trkulja; Tomislav Crnković; Igor Šmigovec; Daniel Matek (Medicinski glasnik, 2017)
Aim: To evaluate biomechanical and clinical outcomes of a newly developed modification of the Wilson's osteotomy for hallux valgus: a three-dimensional subcaptial correction of the metatarsal head position with a simultaneous lateral and plantar shift with derotation intended to reduce displacement of the distal fragment and shortening of the first metatarsal bone. Methods: Thirty four feet (28 female patients) underwent the new procedure and were evaluated before and 12 to 84 months (medi-an=25.5) after the surgery. Results: Plantar shift of the distal fragment was achieved in all feet. Shortening of the first metatarsal was moderate: ?6 mm in 32/34 feet, 7 and 10 mm in the remaining two. Median difference in metatarsal index post-vs. pretreatment was-4.0. The hallux valgus angle, intermetatarsal and distal metatarsal articular angles were reduced in all feet. The American Orthopaedic Foot and Ankle Society score improved in all feet (median increase= 51.5). Conclusion: The method allows for a lateral and plantar shift with derotation of the distal fragment and a mild/moderate shortening of the first metatarsal bone.
Keywords: hallux valgus; surgery; metatarsal